Concepts and derivatives of web services - Khanjani, Atieh; Wan Ab. Rahman, Wan Nurhayati (International Organization of Scientific Research, 2013)
Since the web services are growing rapidly in cloud, service consumers and providers are looking for a means to find better services that satisfy both parties. From both user’s and developer’s perspectives, discovering functional and non-functional characteristics of a web service is essentially considerable. Due to over-coming the above issues many research have been published to improve the usage of web services to satisfy customers. The paper reviews the literature of web services with respect to quality of service (QoS) or non-functional properties, to acquire better understanding of concepts and issues related to QoS web service selecting and discovering processes.